1982
DOI: 10.1148/radiology.143.3.7079490
|View full text |Cite
|
Sign up to set email alerts
|

The pulmonary manifestations of lymphomatoid granulomatosis.

Abstract: The pulmonary manifestations of 5 biopsy-proved cases of lymphomatoid granulomatosis are discussed. Two patients had diffuse reticulonodular infiltration of the lungs, thought to represent infiltrates of lymphomatoid granulomatosis. Three had nodular densities of varying size and distribution, with radiologically normal intervening lung, and biopsy suggested that these represented infarcts; the actual infiltrates of lymphomatoid granulomatosis were below the limits of resolution of the chest radiograph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…Dee et al [9] described two distinct radiographic manifestations of lymphomatoid granulomatosis. In their series, diffuse reticulonodular opacities correlated microscopically with angiocentric granulomatous infiltration without pulmonary infarction, whereas larger masslike opacities corresponded to biopsyproven pulmonary infarcts within lymphomatoid granulomatosis lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dee et al [9] described two distinct radiographic manifestations of lymphomatoid granulomatosis. In their series, diffuse reticulonodular opacities correlated microscopically with angiocentric granulomatous infiltration without pulmonary infarction, whereas larger masslike opacities corresponded to biopsyproven pulmonary infarcts within lymphomatoid granulomatosis lesions.…”
Section: Discussionmentioning
confidence: 99%
“…If recognized early, lymphomatoid granulomatosis can be treated. Radiographically, multiple reticulonodular opacities and masses are present in the lung parenchyma [9,10]. The imaging findings of a series of patients with lymphomatoid granulomatosis have not been described to our knowledge.…”
mentioning
confidence: 99%
“…Dee et al [25] described two distinct radiographic manifestations of LYG. In their series of five patients, diffuse reticulonodular opacities correlated microscopically with angiocentric granulomatous infiltration without pulmonary infarction, whereas larger mass-like opacities corresponded to biopsy-proven pulmonary infarcts.…”
Section: Imaging Findingsmentioning
confidence: 99%
“…They are bilateral and predominate in the lower lobes [34,79,81,82,84,85,88,99,[102][103][104]. The nodules have a peribronchovascular distribution and tend to converge to form pseudotumoural masses and excavate, and can disappear or migrate spontaneously ("wax and wane") [82,88,103] ( fig.…”
Section: Lymphomatoid Granulomatosismentioning
confidence: 99%
“…4). Anatomical-radiological correlation studies have shown that excavated masses correspond to infarcted granulomatosis lesions [104,105]. Unilateral or single nodules, alveolar opacities, and bilateral reticulonodular involvement are more unusual.…”
Section: Lymphomatoid Granulomatosismentioning
confidence: 99%